THE FLEXIBILITY IN A HYBRID LEARNING ENVIRONMENT AFTER COVID-19: A CONCEPT PAPER - Nur Zarifah Mohamad Nazri; Muhammad Ridhwan Mat Zaki (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The pandemic coronavirus disease (COVID-19) has altered the landscape of the education system in every country. As academic institutions throughout the world face the global health issue, there is a need to investigate various instructional approaches such as online, hybrid, and blended learning methods and the impact of these approaches on students’ academic performance. This concept paper aims to investigate the flexibility of hybrid learning environments on student academic performance in Malaysian higher education institutions. Hybrid learning environments, which combine traditional in-person classes with online learning components, have become increasingly popular in Malaysia due to their potential to enhance student learning outcomes and accessibility, especially in their Cumulative Grade Point Average (CGPA). The paper will review relevant literature on the concept of flexibility in hybrid learning environments on student academic performance. This will include a discussion of the benefits and challenges of flexibility, as well as best practices for supporting student success in hybrid learning environments. This paper will conclude with a discussion of the study’s findings for Malaysian higher education institutions and recommendations for optimizing student success in hybrid learning environments. These recommendations may include providing support and resources to enhance student motivation and engagement, promoting clear communication and collaboration between instructors and students, and ensuring access to necessary technology and infrastructure for online learning. By examining the interplay between flexibility and academic performance, this study contributes to the ongoing discourse on hybrid learning effectiveness, aiding educators, and policymakers in refining strategies for optimizing student outcomes.